Redesigning corporate identity that leads increasing sale (case study: Berjaya Air Sdn Bhd) / Wan Mohamad Hakim Zubillah Wan Hassan - Wan Hassan, Wan Mohamad Hakim Zubillah (Faculty of Art and Design, 2013)
Since the birth of flight in 1903, air travel has emerged as a crucial means of transportation for people and products. The hundred-plus years following the invention of the first aircraft have brought about a revolution in the way people travel. The airline business is a major industry, relied upon by millions not only for transportation but also as a way of making a living. Airplanes were around the first few years of the 20th century, but flying was a risky endeavor not commonplace until 1925. In this year, the Air Mail Act facilitated the development of the airline industry by allowing the postmaster to contract with private airlines to deliver mail. Shortly thereafter, the Air Commerce Act gave the Secretary of Commerce power to establish airways, certify aircraft, license pilots, and issue and enforce air traffic regulations. The first commercial airlines included Pan American, Western Air Express and Ford Transport Sen/ice. Within 10 years, many modern day airlines, such as United and American, had emerged as major players. In 2001, the industry dealt with the effects of another economic downturn, as business travel decreased substantially while labor and fuel costs increased. The events 9/11 greatly magnified the airlines' issues, leading to a sharp decline in customers and significantly higher operating costs. Losses continued for years; the industry as a whole didn't return to profitability until 2006. A relatively stable period followed, although controversies arose over service quality and passenger treatment in terms of flight delays, particularly those involving planes waiting on the runway. In 2010 and 2011, the U.S. Department of Transportation issued a series of rules mandating that the airlines provide adequate modifications for passengers in extenuating circumstances.